Recruitment, affiliation, and disengagement among men in terrorist organizations: a systematic review - Zitha, Licínio Zacarias (2024)
Recruitment, affiliation, and disengagement in the context of terrorist groups remain underexplored in a comprehensive, integrated manner. This systematic review is a pioneering effort to address this gap by synthesizing existing knowledge, aiming to analyze the entire trajectory of individuals within terrorist organizations—from recruitment to disengagement—thereby providing a foundation for guiding future research. Conducted through meticulous searches across three major databases—Academic Search Complete, SCOPUS, and the Web of Science Collection—our review followed a pre-registered protocol, ultimately identifying seven studies that met the inclusion criteria. These studies encompass qualitative, quantitative, and mixed-methods research published in peer-reviewed journals, and are accessible in English, Spanish, or Portuguese. Our analysis reveals the critical influence of push and pull factors across these phases, emphasizing that retention is predominantly shaped by individual roles within terrorist organizations and the impact of governmental amnesty policies. Diverging from existing segmented approaches, our findings highlight the importance of examining recruitment, retention, and disengagement as a continuous process to achieve a more comprehensive understanding of terrorist involvement. The insights derived from this study offer valuable guidance for counterterrorism strategies, suggesting interventions targeting recruitment, retention, and recidivism by addressing these crucial factors throughout the entire lifecycle of involvement in terrorist organizations.